The agony of unemployment in the Euro Area - Ristanović Vladimir (Megatrend Revija, 2014)
This paper looks at the evolution of the unemployment problem in the Euro Area. Our goal is to look at what are the roots of the unemployment problem and to devise reasons of the already chronic unemployment problem. We show the main factors that prolong the agony of unemployment and whether it is likely that in the near future, the problem of unemployment in the Euro Area will bi past. In the Euro Area we follow the analysis of basic macroeconomic indicators of balance in an economy - GDP, inflation and unemployment. We consider whether the monetary strategy of inflation targeting has contributed to the unemployment problem, by reducing the potential output, but also to confirm that within the current global crisis there are some deviations from the theoretical concepts of basic macroeconomic relationships - Okun's law and the Phillips curve. We show that only Germany, with a 'small' sacrifice, can save the real sector in the peripheral Mediterranean countries, as well as in the entire Euro Area.